CONTRIBUTION OF SIMULATION TO THE STUDY OF COGNITIVE EXPERTISE IN SPORT - Sebbane, Mohamed; Tahar, Tahar; Nacer, Abdelkader; Adda, Abdedaim; Harchaoui, Youcef (European Scientific Journal, ESJ, 2013)
﻿﻿This study has as its main object to show the effect of categorization of the configurations of play in football. According to Mervis and Rosch (1981), the category is an organization which makes it possible to gather various physical objects or concepts in the same class. This many make us suppose that the elements (i.e., specimens) of the same category have physical features (perceptive) or conceptual (concept) similarities. The main results of this study show, on the one hand, that the experts acquire a rich person repertory of conceptual knowledge by the practice and the experiment and the other hand, through the process of the activity that facilitates the visual data. This operating process of the expert system reduced considerably the space of research. This generally results in an effective and a rapid cognitive performance.